2016
DOI: 10.1111/acer.13275
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivity to Ethanol‐Induced Circadian Rhythm Disruption in Adolescent and Adult Mice

Abstract: Background Growing evidence supports a central role for the circadian system in alcohol use disorders, but few studies have examined this relationship during adolescence. In mammals, circadian rhythms are regulated by the suprachiasmatic nucleus (SCN), a biological clock whose timing is synchronized (reset) to the environment primarily by light (photic) input. Alcohol (ethanol) disrupts circadian timing in part by attenuating photic phase-resetting responses in adult rodents. However, circadian rhythms change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 61 publications
(82 reference statements)
2
14
0
Order By: Relevance
“…Studies of alcohol’s effects on circadian rhythms during development are hampered by the lack of research on developmental changes in rodents’ circadian rhythmicity, despite the fact that circadian activity measures translate easily between rodents and humans. We have recently begun to address this gap in the literature, reporting age-related changes in photic entrainment and larger phase-delays of circadian activity in adolescent mice compared to adults (Ruby et al, 2017), which is consistent with previous reports (Weinert et al, 1994, Weinert and Kompauerova, 1998) and supports one of the proposed mechanisms underlying eveningness in human adolescents (Hagenauer et al, 2009). We also observed insensitivity to the inhibitory effect of acute, moderate-dose ethanol on photic phase-resetting among adolescent mice, suggesting this as a permissive factor for adolescent drinking (Ruby et al, 2017).…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Studies of alcohol’s effects on circadian rhythms during development are hampered by the lack of research on developmental changes in rodents’ circadian rhythmicity, despite the fact that circadian activity measures translate easily between rodents and humans. We have recently begun to address this gap in the literature, reporting age-related changes in photic entrainment and larger phase-delays of circadian activity in adolescent mice compared to adults (Ruby et al, 2017), which is consistent with previous reports (Weinert et al, 1994, Weinert and Kompauerova, 1998) and supports one of the proposed mechanisms underlying eveningness in human adolescents (Hagenauer et al, 2009). We also observed insensitivity to the inhibitory effect of acute, moderate-dose ethanol on photic phase-resetting among adolescent mice, suggesting this as a permissive factor for adolescent drinking (Ruby et al, 2017).…”
Section: Introductionsupporting
confidence: 83%
“…We have recently begun to address this gap in the literature, reporting age-related changes in photic entrainment and larger phase-delays of circadian activity in adolescent mice compared to adults (Ruby et al, 2017), which is consistent with previous reports (Weinert et al, 1994, Weinert and Kompauerova, 1998) and supports one of the proposed mechanisms underlying eveningness in human adolescents (Hagenauer et al, 2009). We also observed insensitivity to the inhibitory effect of acute, moderate-dose ethanol on photic phase-resetting among adolescent mice, suggesting this as a permissive factor for adolescent drinking (Ruby et al, 2017). The present study aimed to characterize the effects of adolescent intermittent ethanol (AIE) exposure on circadian activity in mice both during adolescence and later, in adulthood.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, in our prior studies with vapor exposure, sires were exposed only in adulthood (8–13 weeks of age; [30,31,37,40]). There are well documented differences in EtOH sensitivity [33,41,42] and stress responses [43,44,45] between adolescents and adults. It is unclear if this difference in experimental design impacted outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic reactions produce redox potential that plays an important role in circadian rhythm functioning. Previous studies have suggested that ethanol exposure (both acute and chronic) alters several aspects of the circadian rhythm 36 - 39 .…”
Section: Correlation Between Alcohol Metabolism and Histone Modificatmentioning
confidence: 99%